Tumor Budding Score Is a Strong and Independent Prognostic Factor in Patients With Pancreatic Ductal Adenocarcinoma: An Evaluation of Whole Slide Pathology Images of Large Sections - Jiang, Hui; Yang, Yelin; Qian, Yuping; Shao, Chengwei; Lu, Jianping; Bian, Yun; Zheng, Jianming (Frontiers in Oncology, 2021)
Objective: To develop the tumor budding (TB) score and to explore the association between the TB score and overall survival (OS) in patients with pancreatic ductal adenocarcinoma (PDAC). Methods: In this retrospective study, 130 consecutive patients with PDAC underwent surgical resection between July 2016 and March 2019. The location and counts of TB were assessed based on the digitalized whole slide hematoxylin and eosin images. The TB score was achieved using the Cox regression equation. The cutoff point for the TB score was determined by X-tile. Univariate and multivariate Cox regression models were used to analyze the association between the TB score and OS. Results: The TB score was 0.49 (range 0 to 1.08), and the best cutoff for the TB score was 0.62. The duration of survival in individuals with a low TB score (median: 21.8 months, 95% confidence interval [CI]: 15.43 to 25.50) was significantly longer than that in those with a high TB score (median: 11.33 months, 95% CI: 9.8 to 14.22). Univariate analysis revealed that the TB score was significantly associated with OS (hazard ratio [HR]: 2.71; 95% CI: 1.48 to 4.96; p = 0.001). Multivariate analyses revealed a strong and independent association between the TB score and OS (HR: 2.35; 95% CI: 1.27 to 4.33; p = 0.03). The high TB score group had a 2.14 times higher mortality than the low TB score group. Conclusion: TB score is strongly and independently associated with the risk of OS in PDAC.